The Degree of Practicing Administrative and Technical Efficiencies by Principals of Public Schools in Mafraq Governorate\ Jordan - Al-Shdefat, Muneera Hassan (Journal of Educational and Psychological Sciences, 2020)
The study aimed at finding out the degree of practicing administrative and technical efficiencies by principals of public Schools in Mafraq governorate, and to achieve the goal of the study questionnaire was developed Consisting of (38) paragraph were confirmed validity and reliability, the study sample consisting of (158) Manager, the study results showed that the degree of appreciation and the degree of practicing administrative and technical efficiencies by principals of public Schools in Mafraq governorate from the standpoint of the study sample was a fair degree, the lack of significant differences in the study sample to the reality of the degree of practicing administrative and technical efficiencies by principals of public schools due to the gender and Qualification, the study recommended that in light of these the necessity of preparing and designing training programs for the development of school principals in the light of their technical and administrative efficiencies.
Keywords: Technical and Administrative Efficiencies; jordan; Principals of Schools; Administrative Efficiencies